Acoustic Emission Research and Applications - Sikorski, Wojciech (IntechOpen, 2013)
Acoustic emission (AE) is a phenomenon in which elastic or stress waves are emitted from rapid, localized change of strain energy in material. The practical application of the AE first emerged in the 1950's, but only in the last 20 years the science, technology and applications of AE have progressed significantly. Currently AE has become one of the most important non-destructive testing techniques. This interdisciplinary book consists of nine chapters, which is a proof of the fact that the AE method is continuously and intensively developing and widely applied in: on-line monitoring of civil-engineering structures (e.g. highway bridges, skyscrapers, dams etc.), fatigue cracks detection and location in pressure vessels and pipelines, damage assessment in fibre-reinforced polymer-matrix composites, monitoring welding applications and corrosion processes, bearing condition diagnostics, partial discharge sources detection and location in power transformers and generators, monitoring the drying process of materials, quality evaluation of fruits and vegetables and in otoacoustic emission analysis.